THE ROLE OF THE INDONESIAN MINISTRY OF DEFENSE AGAINST THREATS TO THE AGRICULTURAL SECTOR FROM A NON-MILITARY DEFENSE PERSPECTIVE - Dina Hidayana; Mitro Prihantoro; Herlina J.R. Saragih (The Republic of Indonesia Defense University, 2021)
The agricultural sector is the main element in the food supply, especially to achieve food security, climate change, damage to agricultural infrastructure, land conversion and declining agricultural production are threats in the agricultural sector that are currently occurring both globally and nationally can cause a food crisis. One of the government's efforts to maintain sustainable food availability is the food estate program involving the Ministry of Defense. This study aims to identify the role of the Indonesian Ministry of Defense in overcoming threats to the agricultural sector for the welfare and interests of national defense. This study uses a qualitative method with a literature study approach. The data collection technique is to examine empirical information or data sourced from books, journals, scientific research reports, and other literature that has links to the national defense sector and the agricultural sector, as well as open library materials such as magazines, newspapers, and websites. From the perspective of non-military defense, it can be concluded that the role of defense institutions in overcoming non-military threats, in this case, the threat of a food crisis, is as a form of support capacity in securing national food availability, both production and distribution as well as supporting non-military defense functions in the context of realizing national logistics reserves. To support the implementation of a non-military defense system in agriculture that can maintain the safety of the nation from the threat of a food crisis, it is necessary to empower non-military defense so that it has strong deterrence in preventing all threats that arise.